PROFESSIONAL COMPETENCE OF THE EDUCATOR – THE MAIN FACTOR ENSURING THE QUALITY OF EDUCATION - Rahkmonova Dilnura Saidovna (Journals Park Publishing, 2022)
This article emphasizes the improrance of teachers` competenct in developing a comprehensive personality,the contentand importance of the concept of psychological and pedagogical competence in pedagogy,as well as the fact that a teacher should have the highest possible results in the educational process, with high professionalism and good communication skills provided feedback
Keywords: competence; competency; creativity